Changing Paradigms in Cranio-Facial Regeneration: Current and New Strategies for the Activation of Endogenous Stem Cells - Mele, Luigi; Vitiello, Pietro Paolo; Tirino, Virginia; Paino, Francesca; De Rosa, Alfredo; Liccardo, Davide; Papaccio, Gianpaolo; Desiderio, Vincenzo (Frontiers in Physiology, 2016)
Craniofacial area represent a unique district of human body characterized by a very high complexity of tissues, innervation and vascularization, and being deputed to many fundamental function such as eating, speech, expression of emotions, delivery of sensations such as taste, sight and earing. For this reasons, tissue loss in this area following trauma or for example oncologic resection, have a tremendous impact on patients’ quality of life. In the last 20 years regenerative medicine has emerged as one of the most promising approach to solve problem related to trauma, tissue loss, organ failure etc. One of the most powerful tools to be used for tissue regeneration is represented by stem cells, which have been successfully implanted in different tissue/organs with exciting results. Nevertheless both autologous and allogeneic stem cell transplantation raise many practical and ethical concerns that make this approach very difficult to apply in clinical practice. For this reason different cell free approaches have been developed aiming to the mobilization, recruitment and activation of endogenous stem cells into the injury site avoiding exogenous cells implant but instead stimulating patients’ own stem cells to repair the lesion. To this aim many strategies have been used including functionalized bioscaffold, controlled release of stem cell chemoattractants, growth factors, BMPs, Platelet–Rich-Plasma and other new strategies such as ultrasound wave and laser are just being proposed. Here we review all the current and new strategies used for activation and mobilization of endogenous stem cells in the regeneration of craniofacial tissue.